Gendered Body Mass and Life Satisfaction Among Youth in Three Western European Immigrant-Receiving Countries - Shen, Jing; Kogan, Irena (Frontiers in Sociology, 2021)
In this study we aim to show distinctive patterns of the association between body weight and life satisfaction for adolescent boys and girls, respectively. We understand such patterns by bringing multiple mediating factors into one theoretical framework centred on normative perceptions. By drawing data from the first wave of the CILS4EU that captures 14–15-year-olds in Germany, the Netherlands and Sweden, findings show that psychological factors, indicated by self-esteem and mental state, explain the association between BMI and life dissatisfaction substantially, for both boys and girls. Relationships with parents (particularly among boys) and relationships with peers (particularly among girls) also play significant roles. Moreover, the association between being underweight and life satisfaction among girls varies across ethno-racial groups. Girls originating from Eastern Europe have a tendency to gain more life satisfaction when being underweight, whereas girls rooted in Sub-Saharan African and Caribbean countries display consistently low levels of life satisfaction when being underweight.